Knowledge and Breastfeeding Experience are Associated with High Levels of Exclusive Breastfeeding Self-Efficacy in Pregnant Women from Dobo, Maluku - Christiana Rialine Titaley (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: The rate of exclusive breastfeeding in Indonesia, including Maluku Province, was still low. One of the factors associated with exclusive breastfeeding is maternal self-efficacy. This study aimed to determine factors associated with high levels of exclusive breastfeeding self-efficacy amongst pregnant women living in the catchment area of Dobo and Siwalima Health Centers in Dobo, Aru Islands District, Maluku Province. Methods: This study was conducted in October 2021 using a cross-sectional research design. Using total population sampling, 146 pregnant women living in Dobo and Siwalima Health Center’s catchment area were selected and interviewed. We examined the role of different factors: mothers' sociodemographic characteristics, number of children, breastfeeding knowledge, social support, antenatal care use, and mothers' history of breastfeeding. Logistic regression analysis was performed to determine factors associated with high levels of exclusive breastfeeding self-efficacy in pregnant women. Results: We found that 61.6% of pregnant women had high levels of exclusive breastfeeding self-efficacy. The odds of high levels of exclusive breastfeeding self-efficacy significantly increased in pregnant women with high levels of breastfeeding knowledge (aOR=4.73; 95%CI: 1.44-15.52, p=0.010). The odds also increased in mothers who had ever exclusively breastfed their previous child (aOR = 5.10; 95% CI: 2.02-12.86, p=0.001) or had any experience with breastfeeding (aOR=0.48; 95%CI: 1.88-12, p=0.001). Conclusions: The level of knowledge about exclusive breastfeeding and previous breastfeeding experience was associated with the level of exclusive breastfeeding self-efficacy amongst pregnant women. Health promotion efforts, including health education and provision of support from health workers and family members for pregnant women who did not have any breastfeeding experience, were beneficial to improving exclusive breastfeeding self-efficacy.